Inadvertent puncture of the aortic noncoronary cusp during postoperative left atrial tachycardia ablation - Dursun Aras, MD; Ozcan Ozeke, MD; Serkan Cay, MD; Firat Ozcan, MD; Meryem Kara, MD; Serkan Topaloglu, MD (Journal of Arrhythmia, 2015)
Transseptal catheterization has become part of the interventional electrophysiologist׳s technical armamentarium since the development of left atrial catheter ablation and percutaneous technologies for treating mitral and aortic valve disease. Although frequently performed, the procedure׳s most feared complication is aortic root penetration. Focal atrial tachycardia has been described as the most common late sequela of surgical valve replacements. We present a complicated case involving the inadvertent delivery of an 8 French sheath across the noncoronary cusp during radiofrequency catheter ablation for left atrial tachycardia originating from the mitral annulus in a patient with prior mitral valve replacement.